2015
DOI: 10.1111/cbdd.12559
|View full text |Cite
|
Sign up to set email alerts
|

Improving the Specificity of the Prostate‐Specific Antigen Substrate Glutaryl‐Hyp‐Ala‐Ser‐Chg‐Gln as a Promoiety

Abstract: To develop PSA peptide substrates with improved specificity and plasma stability from the known substrate sequence glutaryl-Hyp-Ala-Ser-Chg-Gln, systematic replacements of the N-terminal segment with D-retro-inverso-peptides were performed with the incorporation of 7-amino-4-methylcoumarin (7-AMC) after Gln for convenient fluorometric determination and ranking of the PSA substrate activity. The D-retro-inverso-peptide conjugates with P2-P5 D-amino acid substitutions were moderate but poorer PSA substrates as c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 29 publications
0
12
0
Order By: Relevance
“…Despite the initially promising results, Dox-PSA did not advance beyond phase I clinical trials. The reasons behind this were likely toxicity concerns as it was shown that in four different species of laboratory animals there was approximately 30-40% non-PSA-mediated prodrug conversion into the active metabolite Dox 13,14 . Aiming at increasing PSA specificity, Aloysius et al modified the initial peptide sequence, Glutaryl-Hyp-Ala-Ser-Chg-Gln, by introducing modifications at position P5, which improved PSA hydrolysis rate and decreased non-PSA-specific cleavage 13 .…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Despite the initially promising results, Dox-PSA did not advance beyond phase I clinical trials. The reasons behind this were likely toxicity concerns as it was shown that in four different species of laboratory animals there was approximately 30-40% non-PSA-mediated prodrug conversion into the active metabolite Dox 13,14 . Aiming at increasing PSA specificity, Aloysius et al modified the initial peptide sequence, Glutaryl-Hyp-Ala-Ser-Chg-Gln, by introducing modifications at position P5, which improved PSA hydrolysis rate and decreased non-PSA-specific cleavage 13 .…”
Section: Discussionmentioning
confidence: 99%
“…Several studies, have used a wide range of liposomes to efficiently deliver a variety of prodrugs, including a number of anticancer agents 36,37 , phospholipid prodrugs 38,39 , antiinflammatory prodrugs 40 and β-blockers prodrugs 41 . Interestingly, previous reports with PSA-cleavable prodrugs have relied on the enzymatically active extracellular PSA to activate the prodrug 13,15,20,42,43 . As a proof-of-concept, in this work we used pH-sensitive liposomes composed of DOPE:CHEMS to ensure a fast and efficient Dox-PSA release inside the acidified endosomes, which is essential for prodrug activation.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations